Financially Literate Or Just Surviving? Mapping MSME Financial Literacy In Makassar City Through The Lens Of Financial Behavior Theory - Fitriani Rahim; Muhaidir Ikram (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Financial literacy among Micro, Small, and Medium Enterprise owners is a critical determinant of business sustainability, particularly in dynamic urban business environments. This study examines the financial literacy profile of MSME owners in Makassar City, Indonesia, using a descriptive quantitative research design grounded in Financial Behavior Theory. Data were collected through a structured questionnaire measuring financial record-keeping literacy, personal and business financial separation, profit and loss literacy, cash flow management literacy, financial planning literacy, financial decision-making literacy, financial statement literacy, and financial risk literacy. The research instrument was tested and confirmed to be valid and reliable before being used for the main analysis. The findings show that the financial literacy of MSME owners in Makassar City is generally in the high category. Personal and business financial separation, as well as financial record-keeping literacy, emerged as the strongest dimensions, indicating that MSME owners tend to recognize the importance of financial discipline and transaction documentation in maintaining business continuity. However, cash flow management and financial risk literacy remain relatively weaker dimensions, suggesting that practical financial behavior is not yet consistently implemented across all aspects of business financial management. These findings indicate that MSME owners may possess adequate conceptual understanding of financial literacy, but still require stronger operational capability in managing liquidity, anticipating financial risks, and using financial information for sustainable business decisions. This study contributes empirical insight into MSME financial literacy in Makassar City and highlights the need for more contextualized financial literacy interventions within the broader Eastern Indonesian MSME ecosystem.